2012
DOI: 10.1038/leu.2012.247
|View full text |Cite
|
Sign up to set email alerts
|

Anti-leukemic mechanisms of pegylated arginase I in acute lymphoblastic T-cell leukemia

Abstract: New treatments for adults with acute lymphoblastic T-cell leukemia (T-ALL) are urgently needed, as the current rate of overall remission in these patients is only about 40 percent. We recently showed the potential therapeutic benefit of the pegylated-human-arginase I (peg-Arg I) in T-ALL. However, the mechanisms by which peg-Arg I induces an anti-T-ALL effect remained unknown. Our results show the induction of T-ALL cell apoptosis by peg-Arg I, which associated with a global arrest in protein synthesis and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 25 publications
1
33
0
2
Order By: Relevance
“…6). In addition to ADI-PEG20 modulating protein turnover as indicated by the MG132-mediated recovery of TS and TK1 enzymes, several other mechanisms may underlie the reduced levels of target proteins, including chemical attack by peroxynitrite, a potent oxidant and nitrating species generated by arginine deprivation (43)(44)(45). More generally, the reciprocal relationship between thymidine and glutamine in ASS1-negative tumors reinforces several other preclinical approaches targeting amino acid utilization in cancer, including methionine, glycine, and serine (46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 86%
“…6). In addition to ADI-PEG20 modulating protein turnover as indicated by the MG132-mediated recovery of TS and TK1 enzymes, several other mechanisms may underlie the reduced levels of target proteins, including chemical attack by peroxynitrite, a potent oxidant and nitrating species generated by arginine deprivation (43)(44)(45). More generally, the reciprocal relationship between thymidine and glutamine in ASS1-negative tumors reinforces several other preclinical approaches targeting amino acid utilization in cancer, including methionine, glycine, and serine (46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 86%
“…Our study identifies GCN2 and its downstream effector eIF2 as essential components that coordinate hepatic mTORC1 during amino acid stress. These data complement and provide mechanistic insight as to why maladaptive activation of hepatic mTORC1 in Gcn2 -/-mice associates with greater morbidity and metabolic toxicity (8) and have important implications for the clinical use of rapidly growing class of GCN2-activating drugs (35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Gcn2 is not an essential gene and so far is found to have 594 missense, 28 nonsense, and 33 frame-shifting mutations in the human population (45).…”
Section: Discussionmentioning
confidence: 97%
“…50 Tumor-specific arginine requirements and the concurrent use of drugs to drive cell death along a particular mechanistic pathway may explain tumor-specific effects of arginine depletion. [51][52][53] RNA sequencing of sensitive and resistant samples identified 20 genes which predict response to arginine depletion. Pathway analysis confirmed that expression of arginine recycling or transport molecules did not correlate with sensitivity to arginine depletion.…”
Section: Discussionmentioning
confidence: 99%
“…61 The bacterial origin of the molecule leads to neutralizing antibody formation and intramuscular injection site hypersensitivity reactions, limiting continued drug administration and a failure to sustain adequately low plasma arginine. 62,63 An alternative PEG human arginase has also been described, in which the enzyme cofactor has been replaced with cobalt to increase arginase activity, 52 but unfortunately seems in early preclinical studies to be significantly more toxic. Thus, the natural enzyme seems to be the best option.…”
Section: Discussionmentioning
confidence: 99%